ELEMENTS OF THE C++ PROGRAMMING LANGUAGE - Botirov Muzaffar Mansurovich (International Journal of Literature and Language Studies, 2026)
In this article, I want to write about the C++ programming language, which is one of the most advanced programming languages in our time. I will briefly write about the history and origin of this language, and in the following articles I will gradually teach you how to write programs in this language. Initially, the UNIX operating system and the C programming language were created, and the C++ language was created based on the C language.